Tinjauan literatur sistematis: Faktor – Faktor Getaran Akibat Transportasi Kereta Api dan Jalan Raya - Dewi Handayani; Lydia Novitriana Nur Hidayati; Rasyid Bintang Ardiansyah; Willy Anastasya Ilonka (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2025)
Transportation plays a crucial role in daily life, supporting the mobility of people, goods, and services. With efficient and well-developed transportation infrastructure, travel time, vehicle wear, and traffic congestion can be significantly reduced, while also fostering local and regional economic development. However, alongside these benefits, transportation also has negative impacts, particularly in the form of vibrations that can affect the surrounding environment. These vibrations can disrupt the comfort and health of the community and cause damage to nearby infrastructure. This underscores the importance of mitigating the effects of vibrations, especially those generated by railway and road transportation. Effective mitigation strategies must begin with understanding of the causes and impacts of these vibrations. This Systematic Literature Review aims to identify the factors that cause vibrations from transportation activities and their effects on both the surrounding environment and the transportation infrastructure itself. The findings are expected to serve as a valuable reference for future research on mitigating transportation-induced vibrations.